Analisis Investasi Online Pada Aplikasi Stockbit - Anggun Suciani Dewi Pratiwi; Dita Ismaida Kurniawan; Fitria Adestiani; Lala Aulia; Abdillah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Along with the issue of financial literacy, data security and privacy are also major concerns in online investment. Use of investment apps requires users to share personal data, potentially creating a risk of privacy breaches. Nguyen and Tran (2020) stated that the design of investment applications influences user adoption, including the level of trust in the security of the data provided by the application. Research methods are ways of research that reduce research variables and operational definitions, sample determination, data types and sources, data collection methods and analysis methods used. This chapter also explains that the research used a qualitative approach. This research shows that the Stokbit application has various features that support investment decision making, ranging from technical analysis, an active community, to education through virtual trading. Although this application provides many benefits, transaction results show that investment success is greatly influenced by the user's financial literacy, the strategy implemented and market conditions. Therefore, the Stokbit application is very suitable for use by novice and professional investors while still paying attention to developing investment skills.